A Model for Causality of Pitching-related Overuse Injuries in Women’s Fastpitch Softball - Holtz, Kaila A.; Zaremski, Jason L.; Janosky, Joseph; Friesen, Kenzie B.; Oliver, Gretchen D. (International Journal of Sports Medicine, 2024)
Fastpitch softball is a popular women’s sport, and athletes, particularly pitchers, are at high risk for overuse injury. Softball-related injury rates are low; however, the prevalence of overuse injuries is high. Injuries at the high school and collegiate levels occur early in the season, and approximately 50% of shoulder and elbow injuries in softball are attributable to overuse. Survey research showed 77% of high school pitchers pitch with pain, and 73% of collegiate pitchers reported an overuse injury in the previous season. Modifiable and non-modifiable intrinsic and extrinsic risk factors contribute to injury risk in a model that can be used in history taking, clinical examination, and management of softball-related injuries. In this manuscript, we present a scoping review of fastpitch softball injury research by competitive levels from 1990 to present. We also introduce a model for overuse injury causality in this athlete population. With this information, clinicians will be able to identify risk factors related to injury in softball pitchers. More research is needed to make evidence-based recommendations for injury prevention in this athlete population.
Keywords: softball; pitching; injuries, epidemiology